Failure Mode and Effects Analysis Under Uncertainty: A Literature Review and Tutorial - Asan, Umut; Soyer, Ayberk (Springer International Publishing, 2015)
The multidimensional nature of risks as well as substantial uncertainties and subjectivities inherent in the risk assessment process led a growing number of researchers to develop alternative approaches for failure mode and effects analysis. The purpose of this chapter is to provide a comprehensive review of the multi-criteria approaches proposed for failure mode and effects analysis under uncertainty and offer a brief tutorial for those who are interested in these approaches.